BUILDING TYPOLOGY OF THE BUCHAN DISTRICT: MORPHOLOGICAL, FUNCTIONAL AND TEMPORAL ANALYSIS - Melnychuk, Hryhorii; Chemakina, Oktyabrina; Kuzmin, Anton; Gnatiuk, Liliia (Theory and practice of design, 2025)
Purpose. The purpose of the study is to identify the typological structure of development in the Bucha district as a foundation for strategic spatial planning, zoning, post-war recovery, and revitalization. Methodology. The methodology combines morphological, functional, and chronological analysis with comparative typological assessment, spatial-statistical synthesis, cartographic zoning, and pilot elements of built environment passportization. As a result, six dominant morphotypes of development are defined, reflecting the spatial differentiation of the district-from traditional rural to post-war chaotic patterns. A functional typology is proposed (agro-residential, recreational-residential, industrial-urban, transit-service, and suburban), along with a chronological stratification of urban fabric. Scientific novelty of the research: for the first time, an integrated typological model of the built environment in the Bucha district has been proposed, combining morphological, functional, and chronological parameters into a unified analytical system. A typological matrix has been developed, encompassing six morphotypes of development, five functional territorial types, and six temporal layers of transformation, enabling a comprehensive characterization of the district’s architectural and spatial structure. The study substantiates the application of typological analysis as an interdisciplinary tool that combines urban planning, sociocultural, historical-geographical, and security components in the formulation of local sustainable development policies. The theoretical value of the research lies in constructing a typological matrix that enables identification of transformation scenarios and integrates historical- morphological knowledge with the imperatives of safety, sustainability, and regional identity. Practical relevance include the application of this typological approach in developing detailed territorial plans, revitalization strategies, and frameworks for post-war urban policy. The proposed method supports spatial integrity, infrastructural modernization, and the preservation of identity, while ensuring functional adaptability and long-term resilience. It offers a basis for systematic spatial passportization of sustainable community structures at the local level.